Academic writing and linguistic awareness - Alberto del Pozo, Luis (2017)
The objective of this article is to explain the relationship between academic writing and linguistic awareness that must be present during the process of preparing, reviewing and controlling research reports. The academic writing uses a formal writing, respectful of the science of language, both in its descriptive aspects and in its prescriptive or normative aspects. Linguistic awareness depends on knowledge of what language is and how it works from the simplest structures of sounds to the complex forms of words, phrases, sentences and paragraphs. Linguistics is the science of language. Its own and distinctive fields are phonetics, semantics and grammar. Let's briefly review each of them.